Pengaruh Kecerdasan Emosional, Budaya Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Plastech Dinamika - Nabilla Chika Fitrianda; Deden Kurniawan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This research aims to determine the influence of emotional intelligence, work culture and work environment on employee performance. Population of PT employees. Plastech Dinamika has 50 employees. Data were collected using a questionnaire with a Likert scale which was processed using SPSS software. The research method used is multiple linear regression. The results of this research show that the Emotional Intelligence variable has a partial effect on employee performance, Work Culture has a partial effect on employee performance and the Work Environment has a partial effect on employee performance. It is hoped that the results of this research can improve employee performance at PT. Plastech Dinamika.